BrokerFi: A DeFi dApp Built upon Broker-based Blockchain - Zheng, Jian; Chen, Qinde; Su, Chunhua; Huang, Huawei (Proceedings - International Conference on Parallel and Distributed Systems, 2023)
A number of promising blockchain scalability technologies such as Rollups, facilitate the fast and cost-effective asset transfer by offloading transactions from a mainchain to sidechains. The proposed broker-based decentralized application (dApp) in this paper, named BrokerFi, also employs a sidechain approach that works as a Layer2 solution on top of a Layer1 blockchain. Comparing with conventional sidechain solutions, the distinct feature of BrokerFi is that the sidechain used in BrokerFi is a sharded blockchain, in which users can stably earn money without economic risks when they stake money to BrokerFi.BrokerFi is designed as a dApp that can offer functionalities to enable users to manage their digital assets and earn money if they join BrokerFi's ecology. Users can change the native tokens issued by BrokerFi using their fiat money. Users can also choose to stake their money in the protocol of BrokerFi and earn profit. We mainly demonstrate the design of BrokerFi in this paper. The significant components of BrokerFi mainly include two parts, i.e., the frontend used by users, and the backend that provides fundamental functionalities for BrokerFi in a Layer2-like sidechain. Experiment results show that the proposed BrokerFi can help clients earn high revenue when their staked tokens follow a low variance.